Evaluation of the environ SRS immobilization mask system for HyperArc: Dosimetric attenuation, dose calculation accuracy, and clinical setup reproducibility - Adi Robinson; Matthew R. Caldwell (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Frameless thermoplastic masks are standard for intracranial stereotactic radiosurgery (SRS), with the Encompass (CQ Medical) widely used on the Varian HyperArc platform. A candidate mask must minimize beam attenuation, permit accurate dose calculation, and enable reproducible setup, yet these are rarely assessed together. Comprehensive comparative data for the proposed Environ (MacroMedics) mask are limited. Purpose To compare the Environ and Encompass masks across three domains: beam attenuation, dose‐calculation accuracy under different algorithm and mask‐contouring conditions, and interfraction setup reproducibility. Methods Attenuation was measured with an ionization chamber in a head phantom (TrueBeam, 6 FFF) at seven static gantry angles and a 0°–180° arc, with an estimated measurement uncertainty budget. Planning accuracy was assessed using HyperArc plans on phantom CT for 1–15 mm PTV margins (single‐target) and 3/5/7 mm (multi‐metastasis), calculated in Eclipse with AAA and Acuros XB (AXB), each with and without the mask in the body contour. Setup reproducibility was analyzed retrospectively from CBCT six‐degree‐of‐freedom corrections (Encompass: 67 fractions/21 patients; Environ: 72 fractions/24 patients). Because repeated fractions are not independent, positioning data were analyzed at the patient level (Mann–Whitney U , Levene's test), by within‐patient reproducibility, and with a confirmatory mixed‐effects model. Results The Encompass attenuated 1.13% ± 0.59% more than the Environ for static beams ( p = 0.002); the arc difference (0.06%) was within uncertainty (∼0.4%, k = 1). The Encompass required mask contouring with AXB for acceptable agreement (2.38% without), whereas the Environ achieved sub‐1% AXB agreement without contouring (0.24%). The Environ showed a smaller mean vertical correction (mixed‐effects p = 0.016) and reduced within‐patient variability in vertical (0.31 vs. 1.25 mm, p < 0.001) and pitch (0.50 vs. 0.99°, p = 0.009); other axes were comparable. Conclusion The Environ performed comparably or favorably across all three domains, supporting it as a clinically acceptable SRS alternative. It achieved acceptable AXB agreement without mask contouring under the conditions tested, though this depends on institution‐specific settings and should be verified locally. The setup‐reproducibility advantages, most robust vertically, are hypothesis‐generating given the retrospective design and absence of intrafraction data.